Edukasi Pelatihan Pengelolaan Sampah Untuk Meningkatkan Sikap Peduli Lingkungan Peserta Didik Sekolah Menengah Kejuruan - Evi Muliyah; Nur Syawalia Fitri; Rachma Gita Irvanto; Muthmainnah; Nazriah Nurunajwa (Forum Kerjasama Pendidikan Tinggi, 2025)
Cleanliness in school environments is a critical factor in creating a comfortable atmosphere, essential for sustaining the educational process. A clean setting, especially in schools, undoubtedly aids in achieving optimal health, thereby enhancing individual productivity. One factor influencing environmental cleanliness is waste management. Proper waste management positively affects both environmental conditions and public health. Conversely, poor waste management adversely impacts these areas. Understanding waste management must be instilled in individuals from an early age. This research aims to foster environmental care attitudes among SMKN 7 South Tangerang students through a waste management educational seminar. Activities included seminars and practical waste management exercises at SMKN 7 Tangsel, involving 39 Culinary Arts students from grade 11. Data collection utilized qualitative methods, including observations, surveys, and documentation. The results indicate a positive change in students' practices and knowledge following the waste management education program.